Health and Healthy Lifestyle Attitudes in University Students - Tatyana G. Svetlichnaya; Elena A. Smirnova; Polina D. Kytina (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
Health is a fundamental human right. The authors studied gender, age, major, and religious commitment as factors that affected attitude towards health and healthy lifestyle in 526 students of the Cherepovets State University, Russia. The survey relied on the questionnaire of Health Attitudes developed by R. A. Berezovskaya. The questionnaire consisted of ten questions distributed by cognitive, emotional, behavioral, and value-motivational scales. Most students demonstrated no definite opinion on health-related issues. In good health, they assessed their mental state as calm, happy, and joyful; however, they denied that bad health could make them experience negative emotions. The students admitted taking no regular health-promoting measures and hesitated to describe the behavioral practices they turn to when sick. They considered themselves neither healthy, nor limited in such resources as time, money, etc. The sample group proved to be rather passive in their attitude towards their own health with an average score of 4.8 points on the value-motivational scale. The survey confirmed the current trend to perceive health not as vital, but as instrumental, i.e., not a goal in itself, but a value that makes it possible to achieve a certain goal.